Advancements in biosurfactant production using agro-industrial waste for industrial and environmental applications - Sundaram, Thanigaivel; Govindarajan, Rasiravathanahalli Kaveriyappan; Vinayagam, Saranya; Krishnan, Vasumathi; Nagarajan, Shankar; Gnanasekaran, Ganesh Raja; Baek, Kwang-Hyun; Rajamani Sekar, Suresh Kumar (Frontiers in Microbiology, 2024)
The adverse effects of waste generation on the environment and public health have raised global concerns. The utilisation of waste as a raw material to develop products with enhanced value has opened up novel prospects for promoting environmental sustainability. Biosurfactants obtained from agro-industrial waste are noteworthy due to their sustainability and environmental friendliness. Microorganisms have been employed to generate biosurfactants as secondary metabolites by making use of waste streams. The utilisation of garbage as a substrate significantly reduces the expenses associated with the process. Furthermore, apart from reducing waste and offering alternatives to artificial surfactants, they are extensively employed in bioremediation, food processing, agriculture, and various other industrial pursuits. Bioremediation of heavy metals and other metallic pollutants mitigated through the use of bacteria that produce biosurfactants which has been the more recent research area with the aim of improving its quality and environmental safety. Moreover, the production of biosurfactants utilizing agricultural waste as a raw material aligns with the principles of waste minimization, environmental sustainability, and the circular economy. This review primarily focuses on the production process and various types of biosurfactants obtained from waste biomass and feedstocks. The subsequent discourse entails the production of biosurfactants derived from various waste streams, specifically agro-industrial waste.